2021
DOI: 10.1123/jpah.2020-0763
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Interrupting Prolonged Sitting With Frequent Bouts of Light-Intensity Standing Exercises on Blood Pressure in Stroke Survivors: A Dose Escalation Trial

Abstract: Background: Interrupting prolonged sitting acutely lowers blood pressure in nonstroke populations. However, the dose–response effect in stroke survivors is unknown. The authors investigated different doses of light-intensity standing exercises that interrupt prolonged sitting and reduce blood pressure immediately and over 24 hours in stroke survivors. Methods: Within-participant, laboratory-based, dose escalation trial. Conditions (8 h) were prolonged sitting and 2 experimental conditions of standing exercises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Reportedly, many factors influence stroke recurrence including age, sex, history of hypertension and diabetes, severity of neurological symptoms, ankle‐brachial index, interleukin‐37 levels, post‐stroke depression, smoking, alcohol consumption, and physical activity level (Han et al., 2021; Hobeanu et al., 2022; Kariasa et al., 2019; Kono et al., 2015; Liu et al., 2020; Skajaa et al., 2022; Wu et al., 2019; Zhang et al., 2021). Additionally, previous studies have shown that sedentary behavior affects stroke recurrence through factors such as arterial stiffness and blood pressure (Batacan et al., 2015; Evans et al., 2019; Hartman et al., 2021; Mackie et al., 2021; Paterson et al., 2020), and guidelines for stroke recurrence recommend reducing sedentary behavior. Therefore, the results of this study indicating that patients engaging in fewer sedentary behaviors have fewer recurrent strokes are well‐supported by the existing literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reportedly, many factors influence stroke recurrence including age, sex, history of hypertension and diabetes, severity of neurological symptoms, ankle‐brachial index, interleukin‐37 levels, post‐stroke depression, smoking, alcohol consumption, and physical activity level (Han et al., 2021; Hobeanu et al., 2022; Kariasa et al., 2019; Kono et al., 2015; Liu et al., 2020; Skajaa et al., 2022; Wu et al., 2019; Zhang et al., 2021). Additionally, previous studies have shown that sedentary behavior affects stroke recurrence through factors such as arterial stiffness and blood pressure (Batacan et al., 2015; Evans et al., 2019; Hartman et al., 2021; Mackie et al., 2021; Paterson et al., 2020), and guidelines for stroke recurrence recommend reducing sedentary behavior. Therefore, the results of this study indicating that patients engaging in fewer sedentary behaviors have fewer recurrent strokes are well‐supported by the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Details of previous randomized controlled trials have been reported (Mackie et al., 2021). Participants were hospitalized for ischemic stroke at an acute care hospital between December 2019 and June 2021.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation